Preemptive Immunotherapy for Minimal Residual Disease in Patients With t(8;21) Acute Myeloid Leukemia After Allogeneic Hematopoietic Stem Cell Transplantation - Fan, Shuang; Shen, Meng-Zhu; Zhang, Xiao-Hui; Xu, Lan-Ping; Wang, Yu; Yan, Chen-Hua; Chen, Huan; Chen, Yu-Hong; Han, Wei; Wang, Feng-Rong; Wang, Jing-Zhi; Zhao, Xiao-Su; et al. (Frontiers in Oncology, 2022)
In patients with t(8;21) acute myeloid leukemia (AML), minimal residual disease (MRD) measured by RUNX1-RUNX1T1 transcript levels could predict relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT). In the present study, we aimed to compare the efficacy of preemptive interferon (IFN)-α therapy and donor lymphocyte infusion (DLI) in AML patients with t(8;21) following allo-HSCT. We also evaluated the appropriate method for patients with different RUNX1-RUNX1T1 transcript levels. In this retrospective study, consecutive patients who had high-risk t(8;21) AML and received allo-HSCT were enrolled if they met the following criteria: (1) was ≤65 years old; (2) and regained MRD positive following allo-HSCT. MRD positive was defined as a loss of a ≥4.5-log reduction and/or the <4.5-log reduction in RUNX1-RUNX1T1 transcripts, and low-level, intermediate-level, and high-level MRDs were respectively defined as 3.5 to 4.5-log, 2.5 to 3.5-log, and <2.5-log reductions in the transcripts comparing with the pretreatment baseline level. Patients with positive RUNX1-RUNX1T1 could receive preemptive IFN-α therapy or DLI, which was mainly according to donor availability and the intentions of physicians and patients. Patients received recombinant human IFN-α-2b therapy by subcutaneous injection twice a week in every 4 weeks cycle. IFN-α therapy was scheduled for 6 cycles or until RUNX1-RUNX1T1 transcripts were negative at least for 2 consecutive tests. The rate of MRD turning negative was 87.5%, 58.1%, and 22.2% for low-, intermediate- and high-level RUNX1-RUNX1T1 patients who received IFN-α as initial therapy, and it was 50.0% and 14.3% for intermediate- and high-level RUNX1-RUNX1T1 patients who received DLI as initial therapy. For the patients with low- and intermediate-level RUNX1-RUNX1T1, the probability of survival at 2 years for IFN-α group was better than that of DLI group (87.6% vs. 55.6%, p=0.003). For the patients with high-level RUNX1-RUNX1T1, the probability of survival was comparable between IFN-α group and DLI group (53.3% vs. 83.3%, p=0.780). Thus, patients with low- and intermediate-level RUNX1-RUNX1T1 might benefit more from preemptive IFN-α therapy compared with DLI. The clinical outcomes were comparable between preemptive IFN-α therapy and DLI for patients with high-level RUNX1-RUNX1T1; however, they should be further improved.